1982
DOI: 10.1001/archotol.1982.00790590015005
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography in the Diagnosis of Deep-Neck Infections

Abstract: \s=b\ Computed tomography (CT) of the neck was used to identify deep-neck abscess formation. Twenty-two patients were screened by CT for deep-neck abscesses. Each patient suspected of having a deep-neck infection underwent CT, often with enhancement if the differential diagnosis included the possibility of a tumor or vascular lesion. Six cases were identified, and these patients were taken to surgery for incision and drainage. There were no false-positives or falsenegatives in the series. In all six cases of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
2

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(15 citation statements)
references
References 9 publications
2
10
1
2
Order By: Relevance
“…Similar to previous studies, our results suggest that CT scans were highly sensitive in diagnosing an abscess (81%) but not very specific (67%) [3,[5][6][7]. Criteria for determining an abscess that have been used by other authors include low density numbers, the presence of air or fluid, and rim enhancement [3,[5][6][7][8]. At our institution, we prefer to use an overall assessment taking in consideration the attenuation of the collection, the presence of a complete enhancing rim and the size of the collection.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to previous studies, our results suggest that CT scans were highly sensitive in diagnosing an abscess (81%) but not very specific (67%) [3,[5][6][7]. Criteria for determining an abscess that have been used by other authors include low density numbers, the presence of air or fluid, and rim enhancement [3,[5][6][7][8]. At our institution, we prefer to use an overall assessment taking in consideration the attenuation of the collection, the presence of a complete enhancing rim and the size of the collection.…”
Section: Discussionsupporting
confidence: 83%
“…The differential diagnosis between abscess and cellulitis is an important issue in management because of the possibility of serious complications without appropriate management. Holt et al [10] reported that CT scans had 100% accuracy in the diagnosis of deep neck abscesses. Miller et al [11] conducted a prospective, blinded comparison of clinical examination and CT scan in deep neck infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1980s, CT of the neck better delineated the soft tissues of the neck, helping to define the presence of an abscess. In fact, because of the reported nearperfect accuracy of CT in differentiating abscesses from phlegmons in some early reports of small case series in the 1980s and early 1990s, 19,20 physicians began to rely heavily on CECT results to dictate their management.…”
Section: Commentmentioning
confidence: 99%